Becoming Radically Undone: Discourses of Identity and Diversity in the Introductory Gender and Women’s Studies Classroom / Ahmed, Sara. 2012a. On Being Included: Racism and Diversity in Institutional Life. Durham, NC: Duke University Press / Wiegman, Robyn. 2012. Object Lessons. Durham, NC: Duke University Press - Thomsen, Carly (Atlantis, 2016)
I suggest here that introductory Gender and Women’s Studies courses must teach students the narratives that feminism tells about itself and of related activist movements and that we also must engage students in critiquing these very narratives. Drawing from Robyn Wiegman’s (2012) Object Lessons and Sara Ahmed’s (2012a) On Being Included: Racism and Diversity in Institutional Life, I argue that feminist teachers must critically interrogate our utilization of discourses of identity and diversity in the feminist classroom.